Multiplex PCR for identification and β-lactam resistance gene detection in clinical isolates of Acinetobacter baumannii - Anh T Nguyen; Trinh C Phan; Thuy BT Ngo; Thanh TT Nguyen; Linh TL Ho; Minh T Quang; Thai M Nguyen (Journal of Infection in Developing Countries)
Introduction: Acinetobacter baumannii (A. baumannii) is a major cause of hospital-acquired infections and frequently harbors antibiotic-resistance genes that complicate treatment. Rapid identification and resistance gene detection are essential for effective antibiotic use and infection control. This study developed a multiplex polymerase chain reaction (PCR) assay to identify A. baumannii and detect key β-lactam resistance genes for clinical isolates.